Avaliação dos efeitos anticonvulsivantes e neuroprotetores da doxiciclina em ratos adultos jovens - Nogueira, Carlos Renato Alves (2008)
Pilocarpine is known to induce convulsions leading to status epilepticus, similar to the temporal lobe epilepsy in humans. In the present work, we evaluated the possible protection affored by doxycyvline, a 2nd generation tetracycline, agaist pilocarpine- induced convulsions in male Wistar rats (P300mg/kg, i.p) in the absence and in the presence of doxicycline (25 to 100 mg/kg i.p.) daily for 7 days.After the pilocarpine injection, all groups were observed for cholinergic signs, latency to the first convulsion and latency to death. Besides, amino acid concentrations in temporal córtices were determined by RP-HPLC, as well catalase activity and levels of TBARS and Nitrite. Results showed that doxycycline did not alter cholinergic signs but increased the latency time to the first convulsion (1.6 to 5 times increase), as compared to P300, and the highest effect was observed with the dose of 25 mg/kg. Similar results were demonstrated to death latency that increased from 1.9 to 9.9 times with doxyciclyne at the doses of 25, 50 and 100 mg/kg. In fact we showed that the pre-treatment with doxycycline decreased in 25% MDA levels, 64% nitrite levels and 67.7% catalase activity. Interestingly, doxycycline decreased glutamate concentrations in 28 and 33% and increased GABA in 112 and 91% at the doses of 50 and 100mg/kg respectively. At the higher dose the drug altered aspartate and taurine concentrations, decreased aspartate levels in 61%, while increasing taurine levels in 34%. Surprisingly, only the lower dose altered glycine levels, increasing its concentration by 132%. In conclusion, we showed that the onset and intensity of pilocarpine-induced seizures were significantly reduced by doxycycline. Furthermore, at least in part, its mechanism of action seems to be mediated by the decrease and increase of excitatory and inhibitory aminoacids, respectively. In addiction the doxycycline capacity to reduce the oxidative stress associated with the pilocarpine-induced may also play a role